2010
DOI: 10.1016/j.compositesb.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the size effects of SiO2 nano-particles on the mechanical properties of binary blended concrete

Abstract: In the current study, the size effects of SiO2 nano-particles on compressive, flexural and tensile strength of binary blended concrete were investigated. SiO2 nano-particles with two different sizes of 15 and 80 nm have been used as a partial cement replacement by 0.5, 1.0, 1.5 and 2.0 wt.%. It was concluded that concrete specimens containing SiO2 particles with average diameter of 15 nm were harder than those containing 80 nm of SiO2 particles at the initial days of curing. But this condition was altered at 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(59 citation statements)
references
References 12 publications
2
55
0
2
Order By: Relevance
“…This value is very close to the nS content that maximizes the density of fresh mortar (1.7%), as reported in a previous paper [38], and is consistent with the findings of other authors [14,23,26].…”
Section: Development Of Compressive Strength Up To 56 Dayssupporting
confidence: 94%
See 1 more Smart Citation
“…This value is very close to the nS content that maximizes the density of fresh mortar (1.7%), as reported in a previous paper [38], and is consistent with the findings of other authors [14,23,26].…”
Section: Development Of Compressive Strength Up To 56 Dayssupporting
confidence: 94%
“…Therefore, there is no consensus regarding the most appropriate range for nS contents, as the values found in current literature are not congruent. It appears that a rule-of-thumb maximum nS content would be 5% over cement weight [7], but other authors have reported that this maximum is 2% over cement weight when the particle size is between 15 nm and 80 nm [26].…”
Section: Introductionmentioning
confidence: 97%
“…This could be due to the unsuitable dispersion of the nanoparticles in the concrete matrix as per previous investigations (Nazari and Riahi, 2011a). The 1% nano-TiO 2 content seems to be an optimal percentage, as it has been already discussed in the literature (Nazari and Riahi, 2011b;Givi et al, 2010;He and Shi, 2008). When compared to the reference mixture, the mixture of 3% nano-TiO 2 has 13% compressive strength decrease after 7 days curing, but only 8% decrease after 28 days curing.…”
Section: Resultsmentioning
confidence: 66%
“…These materials are very effective in changing the properties of concrete at the ultrafine level by the virtue of their very small size. The small size of the particles also means a greater surface area (Alireza Naji Givi, 2010). Since the rate of a pozzolanic reaction is proportional to the surface area available, a faster reaction can be achieved.…”
Section: Nanomaterials-use In Concretementioning
confidence: 99%